Two new species of the bamboo-feeding subgenus Myittana (Benglebra) (Hemiptera: Cicadellidae: Deltocephalinae) from China - Zhao, Yong-Tao; Luo, Qiang; Yang, Lin; Long, Jian-Kun; Chang, Zhi-Min; Chen, Xiang-Sheng (Zootaxa, 2023)
Two new species of the bamboo-feeding genus Myittana (Benglebra) Mahmood & Ahmad, 1969, M. (B.) weiningensis Zhao, Luo & Chen sp. nov. and M. (B.) dongae Zhao, Luo & Chen sp. nov. from China (Guizhou and Guangxi) are described and illustrated. A key to all known species of the subgenus Myittana (Benglebra) is also given.